Neonatal central diabetes insipidus in a case of hydranencephaly - Malik, Sushma; Gandhi, Prachi Shailesh; Mukherjee, Ananya; Shah, Nikita Jaiwant; Lichade, Vinaya Manohar; Wade, Poonam Abhay (Indian Journal of Child Health, 2019)
Neonatal diabetes insipidus (DI) poses both diagnostic and therapeutic challenge to the neonatologists. Neonatal central DI (CDI) is an uncommon disorder which is characterized by polyuria, hypernatremia, high plasma osmolality, and low urine osmolality. Our full-term neonate with an antenatal magnetic resonance imaging showing hydranencephaly presented to us on day 4, with persistent hypernatremic dehydration along with the polyuria which was not getting corrected by the routine management of hypernatremic dehydration. Further investigations revealed urine hypo-osmolality and high serum osmolality and a good response to oral desmopressin (DDAVP). This helped to diagnose CDI secondary to hydranencephaly. The baby was discharged on oral DDAVP, but unfortunately, the baby succumbed at 3 months of age.